Manajemen Pendidikan Islam: Konsep Perencanaan Dalam Al-Qur'an - Roni Harsoyo (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2017)
In the aspect of management, Islamic educational practice is still experiencing weaknesses. Even some experts in the field of Islamic education itself identified as a major weakness. The implementation of education in Islamic educational institutions still embraces the philosophy of ‘asal jalan' which is not rarely used as a single interpretation of the management of education that lilla>hi ta'a>la>. This can be seen from the existence of some Islamic educational institutions that can be said ‘hidup segan matipun tak mau'. But in its development, many Islamic educational institutions have been able to improve themselves and begin to apply modern management rules that are not fully realized with Islamic values, although they must be recognized and derived and developed by Westerners. In such a context, planning plays a very important role in management. Therefore, from this plan a set of decisions can be taken in improving the quality of education. Without good planning, Islamic education institutions will not be advanced and qualified. Planning determines the success or failure of a program, programs that are not through good planning will tend to fail. In a sense, activities as small and big as anything if without any planning are likely to have a chance of failure. Islamic education institutions that do not have good planning will fail. This is certainly increasingly clarify the position of planning in an institution.